The meaning of Ancol's new logo: semiotic analysis of Charles Sanders Peirce - Abdul Basit; Prisca Amandha Oktavia; Rahmi Winangsih; Fitria Santi; Ilham Ramdana (Jurnal Studi Komunikasi, 2024)
Abstract In the first half of 2022, Ancol is rebranding by releasing a new logo. This study uses a qualitative descriptive method with Charles Sanders Peirce's Semiotic Analysis, specifically applying Peirce's Second Trichotomy Theory of Triangle Meaning. Data collection techniques through documentation, literature study, and face-to-face and online interviews via Zoom. The results of this study indicate that the meaning of the message that Ancol wants to convey through its new logo from the visualisation displayed is a depiction of the Ancol parent brand, which presents beach tourism as its main tour and various educational, entertainment and recreational tours with underwater themes as Ancol's sub-brand tourism. The use of ocean blue in the logo represents the tourism identity that Ancol's parent brand presents, namely navy blue for Ancol beach tourism. The “Ancol” typography on the new logo is made with the MVB grenadine font which represents Ancol's vision, especially the letters “C” and “O'' which became an integrated unit like Ancol's vision– to evolve into the most expansive and integrated property development company in Southeast Asia.